A continuous stochastic disaggregation model of rainfall for peak flow simulation in urban hydrologic systems - Cowpertwait, Paul S.P. (Massey University, 2001)
In the paper by Durrans et al. (1999), an algorithm proposed by Ormsbee (1989) is recommended for the stochastic disaggregation of hourly rainfall in continuous flow simulation studies of urban hydrologic systems. However, Durrans et al. found that the method produced a “severe negative bias” in the maximum rainfall intensity of the disaggregated series, so that peak flows in urban systems are likely to be under-estimated by the model. Here we develop a method for disaggregating hourly data to 5min series, which addresses the problem of negative bias. A regression equation is derived for the ratio of the maximum 5min depth to the total depth in the hour. Thus, for any given hourly depth this ratio can be simulated and multiplied by the hourly depth to obtain a 5min maximum. The temporal location of the maximum within the hour can be randomly placed using an appropriate distribution function, e.g. based on a geometrical construction as developed by Ormsbee (1989). The model is developed and tested using 5min rainfall data taken from Lund (1923-39) and Torsgatan (1984-93), Sweden. The results support the use of the model in urban drainage applications.
Keywords: Hydrologic systems; Urban hydrologic systems; Rainfall